GLUCOSE OXIDATION TO FORMIC ACID - Chaerusani, Virdi
Formic acid is a substance that has many advantages. In the near future, formic acid will become a hydrogen carrier substances. This smallest carboxylic acid can be obtained by a glucose oxidation process, which is a renewable resources from starch and very abundant and cheap resources. Glucose can be oxidized with the help of a transtition metal catalyst. Research conducted by Isbell (1973) has prove that in basic condition, 0oC, 1 mole of glucose can quantitatively converted into 6 moles of formic acid with hydrogen peroxide oxidator. C6H12O6 + 6 H2O2 ???? 6 HCOOH + 6 H2O Because hydrogen peroxide is an expensive reagent, it is necessary to generate hydrogen peroxide inside the solution with oxygen from the air and assisted with catalysts. The catalyst used is a combination of copper catalyst which can activate oxygen from air, and manganese, which are known to prevent the formation of reactive oxygen species. The factor variable studied were the molar ratio of the catalyst to glucose 1% and 3%, temperatures 25oC and 75oC, 4 to 8 hours of reaction time. This research is done in base condition. The reaction is done in a three-neck rounded flask as reactor. The reactor is equipped with condensor and thermometer. The quality of the oxidation result is analyzed using silver catalyst. Meanwhile, the quantity of the result is analyzed by iodometric titration. The analysis of the result shows the condition of reaction that resulting higher yield of formic acid for temperature is at 25oC and for reaction time is 4 hours with ratio of copper to mangan y 1:1000. This conditions resulted in glucose conversion of 64.18% and formic acid yield of 46,02%.